Homophilic Dscam interactions control complex dendrite morphogenesis - Hughes, Michael E. (2007)
The morphogenesis of complex dendritic fields requires highly specific patterning and dendrite-dendrite recognition mechanisms. Alternative splicing of the Drosophila cell surface receptor Dscam results in up to 38,016 different receptor isoforms and in vitro binding studies suggested that sequence variability in immunoglobulin-like ecto-domains determines the specificity of strictly homophilic interactions. We report that diverse Dscam receptors play an important role in controlling cell-intrinsic aspects of dendrite guidance. We examined the function of Dscam during morphogenesis of dendrite arborization neurons (“da” neurons) and found that loss of Dscam in single neurons causes abnormal dendritic fasciculation and a strong increase in self-crossing of dendritic branches of da neurons. Restriction of dendritic fields of neighboring class III neurons appeared intact in Dscam deficient neurons suggesting that dendritic self-avoidance but not hetero-neuronal tiling may depend on Dscam function. Over-expression of the same Dscam isoforms in two da neurons with normally overlapping dendritic fields forced a spatial segregation of the two dendritic fields. Taken together, our results suggest that dendritic branches of all four classes of da neurons use isoform-specific homophilic interactions of Dscam to ensure minimal overlap of dendrites. The large pool of Dscam’s extracellular recognition domains may allow the same ‘core’ repulsion mechanism to be used in every da neuron without interfering with hetero-neuronal interactions.